2023
DOI: 10.1177/1934578x231210413
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 Interaction Upregulates YAP1 Expression in HepG2 Cells Through MAPK/ERK Pathway

Shenghao Li,
Muwei Dai,
Fang Wang
et al.

Abstract: Background Antibodies, which target programmed cell death protein-1 (PD-1) or its ligand programmed death ligand-1 (PD-L1), can rescue T cells from an exhausted state and resume their immune response to cancer cells. Clinically, the purpose of blocking the PD-1/PD-L1 signaling pathway is to induce immune cells to play an anti-tumor role. However, the effect of intertumor PD-1/PD-L1 signal blocking on tumor cells remains unclear. Methods HepG2 cells were treated with DHA, IFN-γ, BSA, DDP, PD-1-Fc (1 μg/ml), IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Studies have found that YAP1 inhibitors reduce the expression of PD-L1 in tumor tissues, promote the infiltration of CD8 T cells and CD4 T cells into tumor tissue ( 108 ), which disrupt the immunosuppressive microenvironment of cancer and improve the efficacy of HCC treatment ( 109 ). Interestingly, our research group also found that PD-1/PD-L1 interaction up-regulates YAP1 expression in HepG2 cells through the MAPK/ERK pathway ( 110 ). M2-polarized macrophages stimulated by IgA complex activated YAP/TAZ mediated signaling pathway, inducing cell activation and PD-L1 up-regulation in vitro ( 111 ).…”
Section: Expression Of Pd-l1 In Tumor Cellsmentioning
confidence: 90%
“…Studies have found that YAP1 inhibitors reduce the expression of PD-L1 in tumor tissues, promote the infiltration of CD8 T cells and CD4 T cells into tumor tissue ( 108 ), which disrupt the immunosuppressive microenvironment of cancer and improve the efficacy of HCC treatment ( 109 ). Interestingly, our research group also found that PD-1/PD-L1 interaction up-regulates YAP1 expression in HepG2 cells through the MAPK/ERK pathway ( 110 ). M2-polarized macrophages stimulated by IgA complex activated YAP/TAZ mediated signaling pathway, inducing cell activation and PD-L1 up-regulation in vitro ( 111 ).…”
Section: Expression Of Pd-l1 In Tumor Cellsmentioning
confidence: 90%